COLLEGE EXPERIENCE DURING THE LEARNING PROCESS FOR TEACHING NATURAL SCIENCES IN THE SECONDARY LEVEL - Murakami De La Cruz, Cindy Deiko (2014)
This article seeks to be a source of knowledge and help students and teachers, from the synthesis of the personal college student’s experience in developing their learning to the teaching of natural sciences at the secondary level. In addition, during the development of this article, there are some of the advantages and limitations encountered at this stage of studies contrasted with the reality of education in our country, and it provides a global vision and a neutral point of view about the problems faced by many students during the university life, which often has not been able to be transmitted in its entirety, however, through this document it seeks to break these patterns and improve communication between the authorities and students.